(untitled) (Research, Society and Development, 2020)
The objective was to carry out a narrative review in the view of interprofessional health work to identify the main difficulties and problems faced by women regarding health care, work difficulties and forced coexistence of economic stress and fears about the pandemic. This is a narrative review study, the following search equation was used: (Health AND Woman AND Covid-19) and (Coronavirus OR Covid-19 AND Violence AND Woman) in the following PubMed, Science Direct and VHL. The inclusion criteria were articles with no language limit, studies that report difficulties faced by women, in times of pandemic, full text available and duplicate studies were excluded. The measures of social isolation had a strong impact on women, marked by the increase in domestic violence, domestic work, care for sick children, the elderly and family members and in addition to the services inherent to their profession. In addition, the decrease or absence of habitual physical activity as well as changes in the eating routine end up contributing to changes in nutritional status. Thus, the consequences of the Pandemic and social isolation are greater for more vulnerable social groups, such as women and thus it is essential that health programs are encouraged with strategies that guarantee the right of access to health services and also safety to report situations of abuse.